2008
DOI: 10.1038/sc.2008.155
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative therapy in contusion spinal cord injury

Abstract: Introduction: Some studies have made use of the antioxidative capabilities of high doses of vitamins C and E with the aim of neutralizing the noxious effects of free radicals following spinal cord lesion. Objectives: To evaluate the effects of vitamins C and E, separately and together, on the functional performance of rats that were subjected to standardized spinal cord contusion. Materials and methods: Forty male Wistar rats were used, divided into four groups of 10 animals each. Group 3 received vitamin C 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 14 publications
3
36
1
2
Order By: Relevance
“…For example, neurophysiological changes are commonly detected in asymptomatic patients. 13,21,22 In this study, the BBB scale evaluation showed that rats that received the combined treatment exhibited significantly better recovery than the other groups. This recovery occurred after the 14th day post-SCI.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, neurophysiological changes are commonly detected in asymptomatic patients. 13,21,22 In this study, the BBB scale evaluation showed that rats that received the combined treatment exhibited significantly better recovery than the other groups. This recovery occurred after the 14th day post-SCI.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have also shown functional recovery without an obvious underlying anatomical change in the spinal cord lesion. 13,21,22 The mechanisms that underlie our observations of increased BBB scores and evoked potential tests in experimental rats without evidence of axonal regeneration remain to be discussed and might certainly inspire new research. We found that the combined treatment (exercise plus antidepressant) and the isolated treatments triggered different responses.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] In our protocol we opted for the "MASCIS IMPACTOR" model, which uses weight drop from a standardized height causing spinal cord contusion in rats, after which they are assessed in their locomotor function. 1,2,7 In this experimental study we used Wistar rats due to the low cost and ease in their obtainment. The functional assessment methods are not yet totally standardized, with several descriptions in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Some assessment criteria have been presented in literature, and the scale proposed by Basso, Beattie and Bresnahan, BBB, is that used in this study. 1,2,4 Defined as a scale of 21 points that observes recovery of locomotion in the hind limb after thoracic spinal cord injury in rats, this scale represents a detailed and organized categorization of the recovery of movements in the lower limb following the spinal cord lesion. Each index represents a single and sequential stage of behavioral recovery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation